2019
DOI: 10.2320/matertrans.mbw201807
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Electrochemical Properties of Phases in AB-Type Zr–Ti–Nb–Ni Alloys as Nickel-Metal Hydride Batteries

Abstract: AB-type ZrTiNbNi alloys are good candidates as the negative electrode for Ni-metal hydride (MH) batteries because they have high discharge capacity around 330 mAh g ¹1 at 303 K. The Zr 0.49 Ti 0.5 Nb 0.01 Ni alloy consists of two phases, the primary-phase with B33-type orthorhombic structure and the secondary-phase with B2-type cubic structure. To compare electrochemical properties of each phase with the mother alloy, we synthesized the primary-phase and secondary phase alloys with compositions of Zr 0.54 Ti 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Recently, Matsuyama et al 32 reported experimentally that the enthalpy change for the hydrogenation of Ti‐substituted ZrNi alloys is lower than that of pure ZrNi. Some other studies reported the impact of single substitution with transition metals such as Ti, Cr, Fe, V, and Mn, or with double substitution with Nb and Ti 23,29,30,46 . It was worthwhile to note that, Fe and Mn atoms present the lowest doping concentration (34%) to obtain better dehydrogenation proprieties.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Recently, Matsuyama et al 32 reported experimentally that the enthalpy change for the hydrogenation of Ti‐substituted ZrNi alloys is lower than that of pure ZrNi. Some other studies reported the impact of single substitution with transition metals such as Ti, Cr, Fe, V, and Mn, or with double substitution with Nb and Ti 23,29,30,46 . It was worthwhile to note that, Fe and Mn atoms present the lowest doping concentration (34%) to obtain better dehydrogenation proprieties.…”
Section: Introductionmentioning
confidence: 97%
“…Some other studies reported the impact of single substitution with transition metals such as Ti, Cr, Fe, V, and Mn, or with double substitution with Nb and Ti. 23,29,30,46 It was worthwhile to note that, Fe and Mn atoms present the lowest doping concentration (34%) to obtain better dehydrogenation proprieties. In this work, instead of using transition metals, the proposed alternative approach consists on the investigation of the effect of the substitution with alkaline earth metals Mg, Be, and post-transition metal Al, on the ternary hydride ZrNiH 3 stability in order to further improve its dehydrogenation properties in terms of enthalpy of formation as well its hydrogen storage capacity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations